Comprehensive Analysis of Microsatellite-Related Transcriptomic Signature and Identify Its Clinical Value in Colon Cancer - Luo, Rui; Li, Yang; Wu, Zhijie; Zhang, Yuanxin; Luo, Jian; Yang, Keli; Qin, Xiusen; Wang, Huaiming; Huang, Rongkang; Wang, Hui; Luo, Hongzhi (Frontiers in Surgery, 2022)
Abstract Background Microsatellite has been proved to be an important prognostic factor and a treatment reference in colon cancer. The transcriptome profile and tumor microenvironment of different microsatellite statuses are different. Metastatic colon cancer patients with microsatellite instability-high are sensitive to immune checkpoint inhibitors (ICIs) but not fluorouracil. Efforts have been devoted to identify the predictive factors of immunotherapy. Methods We analyzed the transcriptome profile of different microsatellite statuses in colon cancer by using single-cell and bulk transcriptome data from publicly available databases. The immune cells in the tumor microenvironment were analyzed by the ESTIMATION algorithm. Microsatellite-related signature (MSRS) was constructed by LASSO Cox regression base on differentially expressed genes and its prognostic value and predictive value of response to immunotherapy were assessed. The prognostic value of MSRS was also validated in another cohort. Results Microsatellite instability-high cancers (cells) were clustered differentially in the dimension reduction plot. Most of the immune cells have a higher proportion in the tumor immune microenvironment except for CD56 bright natural killer cells. A total of 238 differentially expressed genes were identified. Based on the 238 DEGs, a neural network was constructed with a Kappa coefficient of 0.706 in the testing cohort. The MSRS is a favorable prognostic factor of overall survival which was also validated in another cohort (GSE39582). Besides, MSRS is correlated with tumor mutation burden in MSI-H colon cancer. However, MSRS is a barely satisfactory factor in predicting immunotherapy with an AUC of 0.624. Conclusion We developed a microsatellite-related signature which is a robust prognostic factor of overall survival in spite of a barely satisfactory immunotherapy predictor. Further studies may need to improve the predictive ability.